Antioxidant Therapeutic Approaches Toward Amelioration of the Pulmonary Pathophysiological Damaging Effects of Ionizing Irradiation - Greenberger, Joel S.; Epperly, Michael W. (Current Respiratory Medicine Reviews, 2007)
There is increasing evidence that lung irradiation damage is mediated by oxidative stress responses of pulmonary vascular and parenchymal cells. The acute irradiation response involves strand breaks in nuclear DNA, then stress activated protein kinase (SAP-Kinase) transport to mitochondria where lipid peroxidation changes lead to cytochrome-c release and apoptosis. However, secondary cytokine elevations lead to a second wave of apoptosis both directly and indirectly mediated through inflammatory cell infiltrates. A recovery phase and latent period follows wherein little structural or physiological evidence of lung damage is detectable in animal models or in humans. The late effects of irradiation pulmonary fibrosis initiate by unknown triggering events thought to involve not only resident pulmonary endothelial cells, but also recruited bone marrow origin macrophages and progenitors of myofibroblasts, which contribute to the lesion of organizing alveolitis in the mouse model or pulmonary irradiation fibrosis in humans. Oxidative stress markers are elevated during formation of the late lesion in a pattern, which is reminiscent of the acute lesion. The amelioration of both the acute and late pulmonary pathophysiologic changes by administration of antioxidant therapies suggests that similar molecular mechanisms may be involved. This article reviews several bodies of evidence concerning the cause and possible therapeutic strategies, which may be of value in treating ionizing irradiation, induced lung damage.
Keywords: radiation fibrosis